Ogilvie-s syndrome in an elderly patient with multi-system atrophy - KOLUKISA, MEHMET; Isik, Ahmet Turan; Kolukisa, MEHMET; Ergun, Fatih; Ahmad, Issam Cheikh (My University, 2013)
Multi-system atrophy (MSA) is characterized by symptoms of autonomic failure, such as orthostatic hypotension and constipation. When intensive bowel motility problems are seen in elderly patients with MSA, Ogilvie Syndrome is kept in mind the management, before surgery.